Estimation of Aggregate and Segment-specific Financial Cycles for a Global Sample of Countries - Amat Adarov (The Vienna Institute for International Economic Studies (wiiw), 2018)
The paper reports estimation results and technical details on the estimation of financial cycles for a global sample of 34 advanced and developing countries over the period 1960Q1–2015Q4, as well as introduces a database of financial cycles. We estimate several versions of financial cycles for credit, housing, bond and equity markets as well as aggregate financial cycles for each country in the sample. To this end we use stationary and non-stationary dynamic factor models and state-space techniques to extract financial cycles as a common factor from a large number of variables conveying price, quantity and risk characteristics of financial markets.
Keywords: F30; E44; G15; 330; financial cycles; global and regional financial cycles; asset bubbles; housing prices; equity; debt securities; credit; capital markets; Kalman filter; factor models